15, 16-Dihydrotanshinone I, a Compound of Salvia miltiorrhiza Bunge, Induces Apoptosis through Inducing Endoplasmic Reticular Stress in Human Prostate Carcinoma Cells. (13th January 2011) - Chuang, Mao-Te; Ho, Feng-Ming; Wu, Chien-Chih; Zhuang, Shao-Yu; Lin, Shyr-Yi; Suk, Fat-Moon; Liang, Yu-Chih
Abstract : 5, 16-dihydrotanshinone I (DHTS) is extracted from Salvia miltiorrhiza Bunge (tanshen root) and was found to be the most effective compound of tanshen extracts against breast cancer cells in our previous studies. However, whether DHTS can induce apoptosis through an endoplasmic reticular (ER) stress pathway was examined herein. In this study, we found that DHTS significantly inhibited the proliferation of human prostate DU145 carcinoma cells and induced apoptosis. DHTS was able to induce ER stress as evidenced by the upregulation of glucose regulation protein 78 (GRP78/Bip) and CAAT/enhancer binding protein homologous protein/growth arrest- and DNA damage-inducible gene 153 (CHOP/GADD153), as well as increases in phosphorylated eukaryotic initiation factor 2α (eIF2α), c-jun N-terminal kinase (JNK), and X-box-binding protein 1 (XBP1) mRNA splicing forms. DHTS treatment also caused significant accumulation of polyubiquitinated proteins and hypoxia-inducible factor (HIF)-1α, indicating that DHTS might be a proteasome inhibitor that is known to induce ER stress or enhance apoptosis caused by the classic ER stress-dependent mechanism. Moreover, DHTS-induced apoptosis was reversed by salubrinal, an ER stress inhibitor. Results suggest that DHTS can induce apoptosis of prostate carcinoma cells via induction of ER stress and/or inhibition of proteasome activity, and may have therapeutic potential for prostate cancer patients.